Intracellular ATP Concentration Contributes to the Cytotoxic and Cytoprotective Effects of Adenosine - Li, Shujue; Li, Xiaofen; Guo, Haiping; Liu, Shouting; Huang, Hongbiao; Liu, Ningning; Yang, Changshan; Tang, Ping; Liu, Jinbao (PLOS ONE, 2013)
Extracellular adenosine (Ade) interacts with cells by two pathways: by activating cell surface receptors at nanomolar/micromolar concentrations; and by interfering with the homeostasis of the intracellular nucleotide pool at millimolar concentrations. Ade shows both cytotoxic and cytoprotective effects; however, the underlying mechanisms remain unclear. In the present study, the effects of adenosine-mediated ATP on cell viability were investigated. Adenosine treatment was found to be cytoprotective in the low intracellular ATP state, but cytotoxic under the normal ATP state. Adenosine-mediated cytotoxicity and cytoprotection rely on adenosine-derived ATP formation, but not via the adenosine receptor pathway. Ade enhanced proteasome inhibition-induced cell death mediated by ATP generation. These data provide a new pathway by which adenosine exerts dual biological effects on cell viability, suggesting an important role for adenosine as an ATP precursor besides the adenosine receptor pathway.